Process Behaviour: Formulae vs. Tests - HENNESSY, MATTHEW (My University, 2010)
Process behaviour is often defined either in terms of the tests they satisfy, or in terms of the logical properties they enjoy. Here we compare these two approaches, using extensional testing in the style of DeNicola, Hennessy, and a recursive version of the property logic HML. We first characterise subsets of this property logic which can be captured by tests. Then we show that those subsets of the property logic capture precisely the power of tests.
Proceedings 17th International Workshop on Expressiveness in Concurrency, Electronic Proceedings in Theoretical Computer Science
17th International Workshop on Expressiveness in Concurrency (Express'10)
PUBLISHED
Paris, France
Keywords: Computer sciences; Process behaviour